Implicature in the Dialogue of 500 Days of Summer Movie by Marc Webb: the Study of Pragmatics - PUSPITA SARI; ANNE JULITZA LITBAGAY (English Journal Literacy Utama, 2019)
The title of this research is ??Implicate in The Dialogue of 500 Days of Summer Movie by Marc Webb: Pragmatics Study??. The topic studied in this research is about implicature that is as a tool of meaning submission implicitly in an utterance. This research aims to identify and analyze types of implicature and levels of intended meaning that appear in the dialog of 500 Days of Summer movie. The method of this research is descriptive analysis method. The descriptive analysis method is a method that explains or describes an object research through analyzed data. The source of data used is taken from the dialog of 500 Days of Summer movie, derived from the website. The results of this research show that there are four types of implicature appear in the dialog of 500 Days of Summer and there are 30 data have been analyzed as implicatures. There are data as generalized conversational implicature, 2 data as scalar implicature, 19 data as particularized conversational implicature, and 8 data as conventional implicature. Besides that, the results show that the implicatures contain intended meanings that have been classified according to the levels of intended meaning. There are 6 data as speaker??s literal meaning, 2 data as speaker??s occasion meaning, 13 data as the hint level, 6 data as the manipulation level, 2 data as the secret deception level, and one utterance as the subconscious or self-deception level. Therefore, it can be concluded that particularized conversational implicature is a dominant implicature and the hint level as a dominant level of intended meaning that appear in the dialog of 500 Days of Summer movie.